2018
DOI: 10.2166/wst.2018.065
|View full text |Cite
|
Sign up to set email alerts
|

Membrane integrated process for advanced treatment of high strength Opium Alkaloid wastewaters

Abstract: In this study, an integrated aerobic membrane bioreactor (MBR)-nanofiltration (NF) system has been applied for advanced treatment of Opium processing wastewaters to comply with strict discharge limits. Aerobic MBR treatment was successfully applied to high strength industrial wastewater. In aerobic MBR treatment, a non-fouling unique slot aeration system was designed using computational fluid dynamics techniques. The MBR was used to separate treated effluent from dispersed and non-settleable biomass. Respirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There is a limited number of studies investigating treatment of opium alkoloid wastewater in the literature. Table 10 summarizes the key performance parameters reported in the literature( [12] and [22]) for different operations. The usage of NF membrane with MBR system enhanced the NF performance.…”
Section: Resultsmentioning
confidence: 99%
“…There is a limited number of studies investigating treatment of opium alkoloid wastewater in the literature. Table 10 summarizes the key performance parameters reported in the literature( [12] and [22]) for different operations. The usage of NF membrane with MBR system enhanced the NF performance.…”
Section: Resultsmentioning
confidence: 99%
“…The removal of organic micropollutants was studied in a baffled OMBR‐MF hybrid system by Pathak, Li, et al (2018), which used an FO membrane rejection process and showed that the removal was greater using an organic draw solute as compared with an inorganic draw solute. Another integrated MBR‐NF hybrid system was evaluated for the treatment of opium processing wastewater, which required a strict industrial wastewater discharge limit (Insel et al., 2018). The study found similar kinetics to municipal activated sludge.…”
Section: Microconstituentsmentioning
confidence: 99%
“…Liu et al demonstrated that a two‐stage AO‐MBR system was beneficial to pollutant removal in landfill leachate, and the average removal efficiencies of chemical oxygen demand (COD) and total nitrogen (TN) were 80.6% and 74.9%, respectively. Insel et al reported that anoxic‐MBR‐nanofiltration (NF) could reduce the COD and TN from 32 000 to 130 mg L −1 , and from 670 to 20 mg L −1 , respectively, in high strength opium alkaloid wastewater. In addition, previous studies indicated that the characteristics of influent, and the operational conditions [such as hydraulic retention time (HRT), sludge retention time (SRT) and return ratio] were important factors that influenced the removal efficiencies of pollutants in MBR‐integrated activated sludge treatment systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies indicated that the characteristics of influent, and the operational conditions [such as hydraulic retention time (HRT), sludge retention time (SRT) and return ratio] were important factors that influenced the removal efficiencies of pollutants in MBR‐integrated activated sludge treatment systems. However, existing studies have focused either on domestic wastewater or on a single type of industrial wastewater, while the removal of composite industrial wastewater in industrial parks has not been well investigated using MBR‐integrated activated sludge systems.…”
Section: Introductionmentioning
confidence: 99%